Changes in serum hepcidin according to thyrometabolic status in patients with Graves' disease. Issue 3 (March 2020) - Krygier, Aleksandra; Szczepanek-Parulska, Ewelina; Filipowicz, Dorota; Ruchała, Marek
Abstract : Introduction: Hepcidin is an acute-phase protein and a key regulator of iron homeostasis. Anaemia frequently occurs in patients with thyroid dysfunction, and hepcidin may be a potential link. Objectives: Prospective assessment of hepcidin serum concentration and other parameters related to Fe homeostasis in hyperthyroid patients in the course of GD at diagnosis and during remission. Patients and Methods: Out of the 70 patients recruited, 42 (32 women, 10 men), aged 42.5 ± 15.1 years, met the inclusion criteria. Clinical and biochemical assessment, including hepcidin measurement by ELISA, was performed at baseline (T0) and after restoration of euthyroidism (T1). Results: Hepcidin concentration at T0 in the 24 patients who completed the study was significantly higher than the value during euthyroidism (28.7 (8.1–39.4) ng/mL vs 7.9 (4.3–12.9) ng/mL, P < 0.001). Hepcidin level was most significantly correlated with ferritin (rho = 0.723) in women at T0. In both men (377 (171–411) vs 165 (84–237) ng/mL, P = 0.001) and women (84 (23–104) vs 35 (16–64) ng/mL, P = 0.001), a significant decrease in ferritin level was demonstrated following therapy. A significant ( P < 0.001) increase in mean corpuscular volume (MCV) (83.5 (82.5–87.1) vs 89.5 (88.8–90.0) fL) and mean concentration of haemoglobin (MCH) (29.0 (28.0–29.4) vs 30.4 (29.5–31.1) pg) was observed. Conclusions: Hepcidin and ferritin decrease significantly during the transition from a hyperthyroid state to euthyroidism in patients with GD. The observed changes occur in parallel to iron homeostasis fluctuations. During the transition from the hyperthyroid state to euthyroidism, the improvement of haematological status is reflected mainly by the increase in MCV and MCH.